Invasive Hemodynamic Monitoring in Acute Heart Failure and Cardiogenic Shock - Luca Baldetti; Marcello Cosenza; Carmine Galdieri; Guglielmo Gallone; Gianluca Ricchetti; Carlo Gaspardone; Beatrice Peveri; Mario Gramegna; Lorenzo Cianfanelli; Francesco Calvo; Vittorio Pazzanese; Marina Pieri; et al. (Reviews in Cardiovascular Medicine, 2025)
Invasive hemodynamic monitoring provides essential information for managing acute heart failure (AHF) and cardiogenic shock (CS) patients, aiding circulatory shock phenotyping and in individualized and hemodynamically-based therapeutic management. The hemodynamic trajectory after the initial care bundle has been provided refines prognostication and anticipates hospital outcomes. Invasive hemodynamic monitoring also tracks the clinical response to supportive measures, providing objective background for therapeutic escalation/de-escalation, facilitating titration of vasoactive/temporary mechanical circulatory support (tMCS) to achieve an optimal balance between native heart function and device assistance, and allowing for a repeated reassessment of hemodynamics during the support weaning phase. Therefore, complete hemodynamic assessment (i.e., arterial line, central venous catheter, and pulmonary artery catheter) is recommended for any patient in overt CS; however, we also provide some pragmatic clinical, imaging, and laboratory criteria to identify patients with beginning stages of CS, which could also benefit from complete invasive hemodynamic assessment. The specific hemodynamic phenotypes that can be applied in clinical practice and case-based examples of how the invasive hemodynamic phenotype can change following therapeutic actions are presented to provide pragmatic guidance on invasive hemodynamic monitoring. This review also aims to summarize the available monitoring technologies, describing the current limitations of each one and the perspective for future developments in the era of artificial intelligence. The gaps in evidence that still characterize pulmonary catheter use, i.e., lack of a robust positive randomized clinical trial in CS, are discussed, along with the wide background of non-randomized studies currently supporting its use in the CS field. The reappraisal of invasive hemodynamic monitoring, closely linked to the advent and increasing adoption of tMCS, sets the stage for greater adoption of this clinical tool in the future, as it remains a fundamental tool for the intensive care cardiologist.